2017
DOI: 10.1021/acs.inorgchem.7b00296
|View full text |Cite
|
Sign up to set email alerts
|

Tris(2-mercaptoimidazolyl)hydroborato Cadmium Thiolate Complexes, [TmBut]CdSAr: Thiolate Exchange at Cadmium in a Sulfur-Rich Coordination Environment

Abstract: A series of cadmium thiolate compounds that feature a sulfur-rich coordination environment, namely [TmBut]CdSAr, have been synthesized by the reactions of [TmBut]CdMe with ArSH (Ar = C6H4-4-F, C6H4-4-But, C6H4-4-OMe, and C6H4-3-OMe). In addition, the pyridine-2-thiolate and pyridine-2-selenolate derivatives, [TmBut]CdSPy and [TmBut]CdSePy have been obtained via the respective reactions of [TmBut]CdMe with pyridine-2-thione and pyridine-2-selone. The molecular structures of [TmBut]CdSAr and [TmBut]CdEPy (E = S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…While the coordination chemistry of borate ligands such as 634 is still receiving considerable interest, , another important facet was added to this field in 1999 by Hill and co-workers, who observed that the B–H bond in complexes of 634 and 635 can be activated to establish boron–metal interactions. Thus, the first metallaboratrane 638 was prepared by reaction of K­( 634 ) with the vinyl complex [Ru­(CHCHCPh 2 OH)­Cl­(CO)­(PPh 3 ) 2 ], which afforded 638 with elimination of the alkene CH 2 CHCPh 2 OH (Scheme ).…”
Section: N-heterocyclic Carbene Adducts Of Group 16 Elementsmentioning
confidence: 86%
See 1 more Smart Citation
“…While the coordination chemistry of borate ligands such as 634 is still receiving considerable interest, , another important facet was added to this field in 1999 by Hill and co-workers, who observed that the B–H bond in complexes of 634 and 635 can be activated to establish boron–metal interactions. Thus, the first metallaboratrane 638 was prepared by reaction of K­( 634 ) with the vinyl complex [Ru­(CHCHCPh 2 OH)­Cl­(CO)­(PPh 3 ) 2 ], which afforded 638 with elimination of the alkene CH 2 CHCPh 2 OH (Scheme ).…”
Section: N-heterocyclic Carbene Adducts Of Group 16 Elementsmentioning
confidence: 86%
“…While the coordination chemistry of borate ligands such as 634 is still receiving considerable interest, 811,812 The molecular structure of this complex revealed octahedral and tetrahedral coordination geometries around the ruthenium and boron atoms, respectively, with a short Ru−B bond length of 2.161( 5) Å (Figure 78). 813 This interaction was described as a metal-to-boron dative bond, making this boron-bridged tris(imidazolin-2-thione) ligand a prominent member of the extensively studied class of ambiphilic σ-acceptor (Z-type) 33 ligands.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…To investigate the effect of anchoring group, 4-aminopyridine was replaced by 2-aminoethanthiol to react with (3-oxopropyl) trimethoxysilan, 17 producing a new imine compound containing a thiolate group denoted as SAET (Scheme 1). Thiolate ligands are of extreme interest in coordination chemistry, 25 because of key function of thiolate groups of cysteine residues in iron and zinc enzymes. 26 They have also found important applications in the elds of nanoscience.…”
Section: Synthesis and Characterization Of Bio-inspired Smnp@saet/metmentioning
confidence: 99%